Study the Glucose Transport, Angiogenesis and Apoptosis Behavioral through Chemotherapy Treatment According to Receptors Status in Women with Breast Cancer (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Glucose transporting into cells, angiogenesis, and apoptosis are the main factors that inducingthe progression of many types of cancers including breast cancer. BC progression was seen as a multi-stepprocess involving progressive changes from normal to hyperplasia with and without atypia, carcinoma insitu, invasive carcinoma, and metastasis.Aim: Assessment the role of glucose transport-1 (GLUT-1), vascular endothelial growth factor (VEGF),and cluster of differentiation factor(CD44) as a glucose transporting into cells, angiogenesis, and apoptoticfactors in women with BC whom receiving chemotherapy.Method and Subjects: 120 women with BC included in this study as a patients group as well as 120apparently healthy women as control. The women with BC is divided into sub-groups depending onchemotherapy treatment status. GLUT-1, VEGF, and CD44 were investigated by ELISA method.Results: This study suggested that highly significant differences in the mean and standard division of GLUT?1and VEGF in all cases of women with BC compare to control group (P-Value< 0.05). The levels of GLUT?1was highly significant difference between two subgroup have Her?2 positive and negative (p < 0.001), andthe levels of VEGF, and CD44 in patients subgroups were significant (p< 0.05).Conclusion: The following up of the progression and responding to chemotherapy treatment may be moreeasy by estimation the glucose transporting, angiogenesis, and apoptotic markers in women with BC.
Keywords: Breast cancer, glucose transport, angiogenesis, apoptosis.